Use of Lignocellulosic Residue from Second-Generation Ethanol Production to Enhance Methane Production Through Co-digestion - Volpi, Maria Paula. C.; Brenelli, Lívia B.; Mockaitis, Gustavo; Rabelo, Sarita C. [UNESP]; Franco, Telma T.; Moraes, Bruna S. (Springer Nature, 2022)
This is a pioneer study evaluating the methane (CH4) production potential from residues of integrated first (vinasse and filter cake) and second (deacetylation pretreatment liquor from straw) generation (1G2G) sugarcane biorefinery, providing a fully chemical characterization of them and their relation with the anaerobic digestion (AD) process. Small-scale assays provided fundamentals for basing the co-digestion optimization by assessing the optimal co-substrates synergistic conditions. Biochemical methane potential (BMP) tests showed co-digestion enhanced CH4 yield of isolated substrates, reaching up to 605 NmLCH4 gVS−1. The association of vinasse and deacetylation liquor as co-substrates increased the BMP by ~ 38% mostly by nutritionally benefiting the methanogenic activity. The kinetic analysis confirmed that the deacetylation liquor was the co-substrate responsible for improving the CH4 production in the co-digestion systems due to the highest CH4 conversion rate. The alkaline characteristic of the liquor (pH ~ 12) also prevented alkalizing from being added to the co-digestion, an input that normally makes the process economically unfeasible to implement on an industrial scale due to the large quantities required for buffering the reactor. The filter cake had the lowest BMP (262 NmLCH4 gVS−1) and digestibility (≤ 40%), further limited by the required stirring to improve the mass transfer of biochemical reactions. The present study drives towards the more sustainable use of vinasse, the most voluminous waste from the sugarcane industry, and lignin-rich residues derived from pretreatment alkaline methods, aiming at an energy-efficient utilization, by at least 16% when compared to the traditional vinasse AD. The experimental and modeling elements from this work indicated the lignin-rich liquor is the main responsible for putting the co-digestion as a disruptive technological arrangement within the 1G2G sugarcane biorefineries, reinforcing the biogas production as the hub of the bioeconomy in the agroindustrial sector.
Keywords: 1G2G ethanol; Biogas; Biorefinery; Deacetylation liquor; Kinetic modeling; Micronutrients